Liberalizing Trade in Services : A Survey - Hoekman, Bernard (World Bank, Washington, DC, 2012)
Since the mid 1980s a substantial amount of research has been undertaken on trade in services. Much of this is inspired by the World Trade Organization or regional trade agreements, especially the European Union, but an increasing number of papers focus on the impacts of services sector liberalization. This paper surveys the literature, focusing on contributions that investigate the determinants of international trade and investment in services, the potential gains from greater trade (and liberalization), and efforts to cooperate to achieve such liberalization through trade agreements. It concludes that there is increasing evidence that services liberalization is an important source of potential welfare gains, but relatively little research has been done that can inform the design of international cooperation-both trade agreements and development assistance-so as to more effectively promote development objectives.